2018
DOI: 10.5327/z2447-211520181800041
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes dos estudantes de enfermagem em relação à pessoa idosa

Abstract: OBJETIVO: Identificar as atitudes dos estudantes de enfermagem em relação à pessoa idosa. MÉTODO: Os estudantes de enfermagem inscritos no segundo ano da licenciatura foram convidados a preencher um questionário no início da unidade curricular de enfermagem geriátrica. Recorreu-se a um estudo quantitativo através da administração da Escala de Atitudes Face aos Idosos de Kogan (KAOP), validada para a população Portuguesa. RESULTADOS: A amostra foi constituída por 39 estudantes que responderam ao instrumento de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(36 reference statements)
1
3
1
Order By: Relevance
“…Unfortunately, only 21.12% (n = 11) expressed a desire to work with elderly people. These results are confirmed by Fernandes et al (2018). The number of students 65.28% (n = 34) who definitely do not want to work with elderly people in the future is significant, and the rest indicated the answer "I have not decided yet".…”
Section: Resultssupporting
confidence: 57%
“…Unfortunately, only 21.12% (n = 11) expressed a desire to work with elderly people. These results are confirmed by Fernandes et al (2018). The number of students 65.28% (n = 34) who definitely do not want to work with elderly people in the future is significant, and the rest indicated the answer "I have not decided yet".…”
Section: Resultssupporting
confidence: 57%
“…According to the research findings, students' responses to variables such as "choosing to live with mother/father or both in the future" and "gender" had a correlation with their total AAS and its subscale scores on contrary to a study contemplating nursing students which yielded statistically no significant relationships between any of the variables such as gender and living with elderly (Fernandes et al 2018). In a different study carried out in Turkey, it was determined that university students' attitudes towards ageism were positive and these attitudes were influenced by gender and desire to work with the elderly after graduation (Gürel, 2019).…”
Section: Discussioncontrasting
confidence: 62%
“…13,14,21,22 However, the finding was similar to those of previous studies. 24,25 It might be due to limited exposure to aged care in the clinical setting that has influenced their work preference in aged care, although the students may have a positive attitude toward older people.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,[21][22][23] However, several studies have reported that there was no significant association between attitudes and work preferences toward older people. 24,25 It was reported that although nursing students have a positive attitude toward older people, they are not interested in aged care. 26,27 The conflicting findings might be attributable to methodological differences such as various ethnicities in prior research studies.…”
Section: Attitudes and Work Preferences Toward Older People Among 199mentioning
confidence: 99%
See 1 more Smart Citation